Analysis of Factors Affecting the Performance of Lecturers in Conducting Research: A Case Study on Private Universities in Medan - Lesmana, Muhammad Taufik; Nasution, Asrizal Efendy (AIBPM Publisher, 2020)
The purpose of this research is to find out and analyze the effect of competence, organizational commitment, leadership and motivation on lecturers' performance in conducting research. This research is descriptive associative. The object is permanent lecturers at private universities in Medan City. The results of this study stated that partially the variables of competence, leadership and motivation have a significant and positive effect on the performance of lecturers in conducting research, while the variable of organizational commitment has no significant and positive effect. Simultaneously the competency, organizational commitment, leadership and motivation variables have a positive and significant effect on the performance of lecturers in conducting research.